2018
DOI: 10.1021/acsomega.7b01830
|View full text |Cite
|
Sign up to set email alerts
|

Purely Inorganic Highly Efficient Ice Nucleating Particle

Abstract: To evaluate the role of atmospheric heterogeneous reactions on the ice nucleation ability of airborne dust particles, we investigated the systematic study of ice nucleation microphysics with a suite of atmospherically relevant metals (10), halides (4), and oxyhalides (2). Within a minute, a kaolin–iron oxide composite (KaFe) showed efficient reactions with aqueous mercury salts. Among the different mercury salts tested, only HgCl 2 reacting with KaFe generated HgKaFe, a highly efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 54 publications
1
33
1
Order By: Relevance
“…Solutions were sonicated for 20 min for ice nucleation for drop–freezing experiments. For each sample, 10 μL droplets were placed on a Pelletier cooling plate (in‐house‐made copper plate) and the plate (which started at approximately 0 °C) was cooled at a rate of 1 °C min −1 . The temperature at which each droplet froze was observed by the naked eye and recorded.…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…Solutions were sonicated for 20 min for ice nucleation for drop–freezing experiments. For each sample, 10 μL droplets were placed on a Pelletier cooling plate (in‐house‐made copper plate) and the plate (which started at approximately 0 °C) was cooled at a rate of 1 °C min −1 . The temperature at which each droplet froze was observed by the naked eye and recorded.…”
Section: Methodsmentioning
confidence: 83%
“…Kaolin contaminated with CuCl 2 was a highly efficient adsorbent, able to take up gaseous elemental Hg within seconds at room temperature (16.33 mg g −1 of Cu from inductively coupled plasma mass spectrometry analysis). Previously, we synthesized Fe composite BHFe from the reduction of FeCl 2 by NaBH 4 followed by aerial oxidation. BHFe is an efficient Hg II adsorbent and produced a highly efficient ice‐nucleating particle HgBHFe (maghemite@Hg 2 Cl 2 ) after the uptake of HgCl 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant bacteria such as Pseudomonas syringae are deemed omnipresent in the atmosphere and precipitation (Despres et al, 2012;Stopelli et al, 2017;Morris et al, 2014), and facilitate cloud ice formation up to −1 °C (Despres et al, 2012). While, only a few laboratory-based studies have reported known inorganic or mineral materials that ice nucleation activity at such temperatures (Ganguly et al, 2018;Atkinson et al, 2013). Mineral and soil dust serving as atmospheric shuttles for organic microbial fragments can be transported thousands of kilometres and serve as effective INPs, even from highly arid regions such as the Sahara (Kellogg and Griffin, 2006), yet the exact origin of the ice nucleation germ forming at the warmest temperatures is speculated to be due to the ice binding proteins or macromolecules of the biological components (O'Sullivan et al, 2014;O'Sullivan et al, 2016;Conen and Yakutin, 2018).…”
mentioning
confidence: 99%